Managing only with transparency: The strategic functions of ignorance. (September 2018) - Roberts, John
Abstract: This paper offers a supplement or qualification to earlier arguments for the potentials of 'intelligent accountability'. It explores the genesis and dynamics of its antithesis; a self-conscious choice by managers to focus exclusively on fulfilling, or being seen to fulfil, the demands of external transparency. Whilst 'decoupling' was originally conceived as a way for organisations to meet external pressures without compromising operational efficiency, the paper suggests that managing only with transparency serves to produce a less happy and more consequential decoupling whose contradictions are focused in management/staff relations. The paper builds on recent discussions of 'tight coupling', 'functional stupidity' and the importance of 'spectacle' in contemporary organisations to explore the dynamics of managing only with transparency; an exclusive focus on managing only what is transparent. It suggests that this can prove functional for managers as a way to deny any dependence on local knowledge, and avoid engagement with the complexity of operational interdependencies. However, it leaves staff to manage for themselves the demands of operational integration; a task made more difficult by the contradictions and conflicts created by the intrusion of managerial demands to meet ill-informed and thereby ill-conceived targets and objectives. In this way ignorance is knowingly and actively cultivated by management, whilst intelligence and reflection are self-censored out of organisational processes by subordinates. The analysis serves to further illustrate the power of transparency to play upon and mobilise a narcissistic preoccupation with either the defence or advancement of the self.